2018
DOI: 10.21923/jesd.359667
|View full text |Cite
|
Sign up to set email alerts
|

Basketbol Oyuncularinin Antropometri̇k Özelli̇kleri̇ İle Bazi Performans Değerleri̇ Arasindaki̇ İli̇şki̇ni̇n İncelenmesi̇

Abstract: Bu çalışmada Bursa ilindeki Botaş Basketbol Takımı Minikler grubu (8-10 yaş) ve Yıldızlar grubu (14 yaş) erkek çocukların antropometrik özellikleri ile bazı performans değerleri ölçülerek, antropometrik veriler ile performans arasındaki ilişkilerin incelenmesi amaçlanmıştır. Minikler grubundan 25, yıldızlar grubundan 8 çocuk olmak üzere toplam 33 erkek oyuncudan oluşan örneklem grubu ile yapılan bu çalışmada; basketbol performansı ile ilgili olabilecek uzunluklar, çevresel ölçüler ve deri kıvrımı kalınlıkları … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In Akyüz et al (2013) study with basketball national team athletes, showed that there was a statistically significant relationship between right grip force and left grip force values and back force and leg force values. Ulusu et al (2018) in their study, 20 meters speed and horizontal jump performances of basketball players with arm, foot, stroke length, leg length, knee height, foot width, arm, thigh, calf circumference have found a positive relationship. Gencer et al (2019) examined the relationship between basketball players' dominant and non-dominant grip strength and free throw hit rates.…”
Section: Discussionmentioning
confidence: 85%
“…In Akyüz et al (2013) study with basketball national team athletes, showed that there was a statistically significant relationship between right grip force and left grip force values and back force and leg force values. Ulusu et al (2018) in their study, 20 meters speed and horizontal jump performances of basketball players with arm, foot, stroke length, leg length, knee height, foot width, arm, thigh, calf circumference have found a positive relationship. Gencer et al (2019) examined the relationship between basketball players' dominant and non-dominant grip strength and free throw hit rates.…”
Section: Discussionmentioning
confidence: 85%